GhJAZ2 attenuates cotton resistance to biotic stresses via the inhibition of the transcriptional activity of GhbHLH171. (25th September 2017) - He, Xin; Zhu, Longfu; Wassan, Ghulam Mustafa; Wang, Yujing; Miao, Yuhuan; Shaban, Muhammad; Hu, Haiyan; Sun, Heng; Zhang, Xianlong
Summary: Plants have evolved effective mechanisms to protect themselves against multiple stresses, and employ jasmonates (JAs) as vital defence signals to defend against pathogen infection. The accumulation of JA, induced by signals from biotic and abiotic stresses, results in the degradation of Jasmonate‐ZIM‐domain (JAZ) proteins, followed by the de‐repression of JAZ‐repressed transcription factors (such as MYC2) to activate defence responses and developmental processes. Here, we characterized a JAZ family protein, GhJAZ2, from cotton ( Gossypium hirsutum ) which was induced by methyl jasmonate (MeJA) and inoculation of Verticillium dahliae . The overexpression of GhJAZ2 in cotton impairs the sensitivity to JA, decreases the expression level of JA‐response genes ( GhPDF1.2 and GhVSP ) and enhances the susceptibility to V. dahliae and insect herbivory. Yeast two‐hybrid and bimolecular fluorescence complementation assays showed that GhJAZ2 may be involved in the regulation of cotton disease resistance by interaction with further disease‐response proteins, such as pathogenesis‐related protein GhPR10, dirigent‐like protein GhD2, nucleotide‐binding site leucine‐rich repeat (NBS‐LRR) disease‐resistant protein GhR1 and a basic helix–loop–helix transcription factor GhbHLH171. Unlike MYC2, overexpression of GhbHLH171 in cotton activates the JA synthesis and signalling pathway, and improves plant tolerance to the fungus V. dahliae . Molecular and genetic evidence shows that GhJAZ2 can interact with GhbHLH171 and inhibit its transcriptional activity and, as a result, can restrain the JA‐mediated defence response. This study provides new insights into the molecular mechanisms of GhJAZ2 in the regulation of the cotton defence response.